Visual Studio Code distilled : evolved code editing for Windows, MacOS, and Linux - Del Sole, Alessandro (Apress, 2021)
Use Visual Studio Code to write and debug code quickly and efficiently on any platform, for any device, using any programming language, and on the operating system of your choice. Visual Studio Code is an open source and cross-platform development tool that focuses on code editing across a variety of development scenarios, including web, mobile, and cloud development. This second edition of Visual Studio Code Distilled has been updated and expanded with two new chapters on writing apps with Python and building apps for the cloud and deployment to Azure. The book teaches you how to be immediately productive with Visual Studio Code, from the basics to some of the more complex topics. You will learn how to work on individual code files, complete projects, and come away with an understanding of advanced code-editing features that will help you focus on productivity, and source code collaboration with Git. What You Will Learn Get started with practical guidance on Visual Studio Code, including expansive guidance on writing apps with C# and Python Comprehend Visual Studio Code in a way that is not just theory or a list of features, but an approach driven by developer tasks and needs Understand integrated support for team collaboration with Git for executing and debugging code, and the many ways you can extend and customize Visual Studio Code Debug code on multiple platforms through real-world guidance, such as working under corporate networks Expand your coding intelligence from web to mobile to the cloud Acquire valuable tips, tricks, and suggestions from hard-earned, real-world experience to be more productive This book is for all developers (including JavaScript, Java, NodeJS), not just those with a Microsoft background, who will benefit from learning and using VS code as a cross-platform and cross-language tool. Alessandro Del Sole is Senior Software Engineer for a healthcare company, building mobile apps for doctors and dialysis patients. He has been in the software industry for more than 20 years, focusing on Microsoft technologies such as .NET, C#, Visual Studio, and Xamarin. He has been a trainer, consultant, and a Microsoft MVP since 2008 and is the author of many technical books. He is a Xamarin Certified Mobile Developer, Microsoft Certified Professional, and a Microsoft Programming Specialist in C#.